2020
DOI: 10.1002/bit.27611
|View full text |Cite
|
Sign up to set email alerts
|

Identification of preferred multimodal ligand‐binding regions on IgG1 FC using nuclear magnetic resonance and molecular dynamics simulations

Abstract: In this study, the binding of multimodal chromatographic ligands to the IgG1 FC domain were studied using nuclear magnetic resonance and molecular dynamics simulations. Nuclear magnetic resonance experiments carried out with chromatographic ligands and a perdeuterated 15N‐labeled FC domain indicated that while single‐mode ion exchange ligands interacted very weakly throughout the FC surface, multimodal ligands containing negatively charged and aromatic moieties interacted with specific clusters of residues wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 67 publications
2
16
0
Order By: Relevance
“…To facilitate the discussion, both the cartoon and surface representations of the protein surface are presented in the figure. As can be seen, the μM K D,app values obtained from NMR experiments with the NPs (Figure ) were 3 orders of magnitude smaller than those obtained previously with these ligands in solution . These results clearly indicate enhanced binding of the F C to MM-functionalized surfaces.…”
Section: Results and Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…To facilitate the discussion, both the cartoon and surface representations of the protein surface are presented in the figure. As can be seen, the μM K D,app values obtained from NMR experiments with the NPs (Figure ) were 3 orders of magnitude smaller than those obtained previously with these ligands in solution . These results clearly indicate enhanced binding of the F C to MM-functionalized surfaces.…”
Section: Results and Discussionmentioning
confidence: 55%
“…Briefly, residues that exhibited linear migration trajectories with saturation behavior were fit to the N-site binding model, as described in eq . As described in the Materials and Methods section, a geometric analysis was carried out to estimate the maximum number of Fc molecules that could bind to a single NP, assuming that the side face of the F C was the primary interacting binding region, as has been reported previously by our group . The results of this analysis indicated that there were at most 26 (N) binding sites (note: this calculation assumed that multiple ligand head groups could interact with a single residue/cluster of residues on the F C surface).…”
Section: Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…While these biophysical studies provided valuable insights into the nature of protein-ligand interactions in multimodal systems, the work had been limited to small model proteins. Recently, our group has employed NMR to identify preferred binding regions for IgG1 Fc interacting with multimodal cation exchange (MM CEX) and CEX resin systems (Gudhka et al, 2021).…”
Section: Introductionmentioning
confidence: 99%